Sosialisasi Karakter Entrepreneur Muda Bagi Siswa SMK Negeri 1 Pangkalpinang - Mulyani, Hendarti Tri Setyo; Maharani, Yunita (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service is aimed at students of SMK Negeri 1 Pangkalpinang, this can provide an overview in order to prepare themselves to become successful young entrepreneurs by starting various productive businesses. Planting and prioritizing the entrepreneurial spirit since school is the basic foundation for building courage and motivation to improve welfare through creative ideas and skills that are owned, this can help the government in the problem of unemployment and reduce poverty. In addition, the role of teachers and lecturers must be able to explore student competencies not only in terms of intelligence, but also focus on shaping morals and building student character in entrepreneurship. The success of this community service activity can be measured from two achievements, including all series of service events running smoothly without hindrance, and the material on the spirit of young entrepreneurs has been received and practiced by students. The questionnaire results showed an increase in students' knowledge about entrepreneurship. The accumulated answers to the questionnaire showed that 45% of the participants strongly agreed with the entrepreneur training and 55% agreed. The outcomes of this service include that students in accordance with the focus on each of their vocations become job-ready graduates such as becoming entrepreneurs, exporters or international trade.